Flow Cytometric Detection of Circulating Osteosarcoma Cells in Dogs. Issue 9 (7th July 2019) - Wright, Tanya; Brisson, Brigitte A.; Wood, Geoffrey A.; Oblak, Michelle; Mutsaers, Anthony J.; Sabine, Victoria; Skowronski, Karolina; Belanger, Catherine; Tiessen, Angela; Bienzle, Dorothee
Abstract: Osteosarcoma (OSA) is a malignant tumor of middle‐aged dogs and adolescent humans. The clinical outcome of OSA has not improved over more than three decades, and dogs typically succumb to metastatic disease within 6 months despite tumor resection through limb amputation and adjuvant chemotherapy. Therefore, undetectable tumor cells with potential to form metastases are present at diagnosis. An assay to identify canine immortalized and primary OSA cells through flow cytometric detection of intracellular collagen 1 (Col I) and osteocalcin was optimized, and applied to blood samples from tumor‐bearing dogs for detection of circulating tumor cells (CTCs). Spiking variable number of OSA cells into normal dog blood recovered 50–60% of Col I positive cells with high forward and variable side light scatter. An algorithm to exclude nonviable, doublet, and autofluorescent cells was applied to sequential blood samples from three dogs obtained prior to and after limb amputation, and at approximately, triweekly intervals over 121, 142, and 183 days of chemotherapy, respectively. Dogs had >100 CTC/10 6 leukocytes prior to amputation, variably frequent CTC during chemotherapy, and an increase up to 4, 000 CTC/10 6 leukocytes within 4 weeks before overt metastases or death. Sorted CTCs were morphologically similar to direct tumor aspirates and positive for Col I. Although preliminary, findings suggest that CTCs are frequent in canine OSA, more numerous than carcinoma CTC in humans, and that an increase in CTC frequency may herald clinical deterioration. This assay may enable enumeration and isolation of OSA CTC for prognostic and functional studies, respectively. © 2019 International Society for Advancement of Cytometry Abstract :